The Sex of Class : Women Transforming American Labor - Cobble, Dorothy Sue (Book collections on Project MUSE., 2007)
Women now comprise the majority of the working class. Yet this fundamental transformation has gone largely unnoticed. This book is about how the sex of workers matters in understanding the jobs they do, the problems they face at work, and the new labor movements they are creating in the United States and globally. In The Sex of Class, twenty prominent scholars, labor leaders, and policy analysts look at the implication of this "sexual revolution" for labor policy and practice. The Sex of Class introduces readers to some of the most vibrant and forward-thinking social movements of our era: the clerical worker protests of the 1970s; the emergence of gay rights on the auto shop floor; the upsurge of union organizing in service jobs; worker centers and community unions of immigrant women; successful campaigns for paid family leave and work redesign; and innovative labor NGOs, cross-border alliances, and global labor federations. Revealing the animating ideas and the innovative strategies put into practice by the female leaders of the twenty-first-century social justice movement, the contributors to this book offer new ideas for how government can help reduce class and sex inequalities. They assess the status of women and sexual minorities within the traditional labor movement and they provide inspiring case studies of how women workers and their allies are inventing new forms of worker representation and power